Leadership skills of the Coffee Shop Supervisors in Metro Manila : an assessment - Atanacio, Andrea; Azurin, Elizah April; Estrella, Anjela Vinyl; Olyares, Myra; Perez, Eric Jasper (Manila : National University, 2011)
A supervisor is the lowest, or most-junior, management position. It is usually a step above lead (Accounting Supervisor is senior to Lead Accounting Specialist), but below manager.
Title Page -- Approval Sheet -- Acknowledgement -- Table of Contents -- List of Figures -- Abstract -- Chapter I. The Problem and its Background -- Chapter II. Review of Related Literature -- Chapter III. Research Methodology -- Bibliography -- Appendices -- Curriculum Vitae.
Includes bibliographical references.